Dasar-dasar Filosofis Ilmu Olahraga - Pramono, Made (Jurnal Filsafat "WISDOM", 2003)
Sport in our society is a part of common daily activity, and also is an art of competition. Various aspects involved in sports events such as human resources, building, investment, equipments, and anyother needs. Internal probelms such as efforts to gain the best position in local, national, and international events implicate so many other probelms. Beside those probelms, sport develops in any scientific studies like Psychology of Sport, Politics of Sport, Law Study of Spoert, etc. All of those scientific studies are dimensions in which sport requires an academic consicnce in investagating philosophical foundations of sport as science.